2014
DOI: 10.1254/jphs.14134fp
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Opioid-Induced Rewarding Effects Under Oxaliplatin- and Paclitaxel-Induced Neuropathy in Rats

Abstract: IntroductionAlthough m-opioid receptor agonists such as morphine, oxycodone, and fentanyl have prominent antinociceptive effects, they also have adverse effects (e.g., emesis, constipation, drowsiness, and psychological dependence). Psychological dependence on opioids is a serious problem worldwide, and one of the triggers for inducing such opioid dependence is the inappropriate use or overdose of prescribed m-opioid receptor agonists (1). It is widely accepted that psychological events such as the reinforcing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
4
9
1
Order By: Relevance
“…In the CPP experiments, paclitaxel-induced allodynia failed to alter significantly the effects of morphine relative to saline-treated control male and female mice. Our observation that the susceptibility to morphine’s conditioned rewarding effects remains unaltered as a function of paclitaxel treatment is consistent with a recent report in male rats where the conditioned rewarding effects of opioids such as 4 mg/kg morphine, 0.056 mg/kg oxycodone, and 0.017 mg/kg fentanyl, administered subcutaneously, were not altered in the presence of paclitaxel- and oxaliplatin-induced treatment (Mori, et al, 2014). However, our results are in contrast to the reports indicating either an increase (Cahill CM, 2013; Sufka, 1994) or a decrease (Suzuki, Kishimoto, & Misawa, 1996) (Niikura, Kobayashi, et al, 2008; Niikura, Narita, et al, 2008; Ozaki, et al, 2003; Ozaki, et al, 2002; Ozaki, et al, 2004) in opioid reward using alternative chronic pain models such as persistent inflammatory pain and neuropathic pain from nerve injury in male rats and mice.…”
Section: Discussionsupporting
confidence: 92%
“…In the CPP experiments, paclitaxel-induced allodynia failed to alter significantly the effects of morphine relative to saline-treated control male and female mice. Our observation that the susceptibility to morphine’s conditioned rewarding effects remains unaltered as a function of paclitaxel treatment is consistent with a recent report in male rats where the conditioned rewarding effects of opioids such as 4 mg/kg morphine, 0.056 mg/kg oxycodone, and 0.017 mg/kg fentanyl, administered subcutaneously, were not altered in the presence of paclitaxel- and oxaliplatin-induced treatment (Mori, et al, 2014). However, our results are in contrast to the reports indicating either an increase (Cahill CM, 2013; Sufka, 1994) or a decrease (Suzuki, Kishimoto, & Misawa, 1996) (Niikura, Kobayashi, et al, 2008; Niikura, Narita, et al, 2008; Ozaki, et al, 2003; Ozaki, et al, 2002; Ozaki, et al, 2004) in opioid reward using alternative chronic pain models such as persistent inflammatory pain and neuropathic pain from nerve injury in male rats and mice.…”
Section: Discussionsupporting
confidence: 92%
“…Second, paclitaxel also failed to alter the trajectory of increasing morphine reward produced by repeated morphine administration. This supports a previous study that found no effect of paclitaxel on morphine-induced conditioned place preference in rats (Mori et al, 2014) and extends these studies by showing a failure of paclitaxel to alter the changes in morphine reward that occur with initial exposure to a regimen of repeated morphine treatment. It is especially relevant to note that repeated morphine administration produced increasing expression of reward while producing decreased expression of (i.e., tolerance to) antiallodynia.…”
Section: Effects Of Morphine In Rats With Chemotherapy-induced Neuropsupporting
confidence: 90%
“…After the normal paw pain threshold of the animal groups was measured using a Basile ® algesimeter (18), a daily single dose of 2 mg kg −1 paclitaxel was intraperitoneally administered to the rats in the PAC, PAC-50 and PAC-100 groups for a total of four times on days 1, 3, 5 and 7, with a twoday interval between each administration (17,19). At the end of day 7, 50 mg kg −1 and 100 mg kg −1 doses of anakinra were intraperitoneally injected to the rats in the PAC-50 and PAC-100 groups, respectively.…”
Section: Methodsmentioning
confidence: 99%